What role can planted fallows play in the humid and subhumid zone of West and Central Africa? - Hauser, S.; Nolte, C.; Carsky, R.J. (Springer, 2007)
Crop management without fertilizer input, which is commonly practiced by most farmers in the humid forest zone of West and Central Africa, requires soil fertility replenishment during a fallow period. Hypothetical relationships between fallow length and crop yields assume, that after the cropping phase replenishment starts with high annual increments, leading to an early recovery of most soil fertility, then slowly approaching a maximum level. The few available empirical data, however, indicate that this assumption is wrong. Within the first 8 years of fallow, biomass and nutrient accumulation is either progressive (low initial increments) or linear. Planted fallows are supposed to replenish soil fertility faster or to higher levels than natural regrowth and should thus lead to higher crop yields. Two major types of planted fallow are distinguished: tree-based and herbaceous fallows. Data from West and Central Africa do not confirm that tree based fallows are generally capable of attaining higher crop yields than natural regrowth or other planted fallows. The majority of experiments with tree-based fallows showed no differences to the control (60.0%). Crop yield declines were found in 15.7% of cases, and only 24.3% resulted in significant yield increases. Changes in soil properties were more frequently positive (34.3%) than negative (9.8%), yet, most often (55.9%), there was no effect. Herbaceous fallow had dominantly positive effects on crop yields (52.5% of cases), with only 3% of cases in which significant reductions were observed. Positive features of some herbaceous fallows, such as easy establishment, rapid weed suppression, and labor efficient slash-and-burn crop establishment make the technology more likely to be accepted and adopted by farmers. It appears that fallows have to be specifically designed for responsive crops, i.e. maize. It is unlikely that one type of fallow can serve the multitude of crops and intercrops grown in the region. Depending on the major constraints to crop production or income generation, planted fallows have to be specifically designed to address these constraints. This may require de-emphasizing the soil fertility aspect and focusing on marketable fallow by-products, weed and pest suppression and reduced labor requirements. Thus, future impact through research on planted fallows will depend on exact targeting of specific fallow types and species to the most responsive crops and to explicit farmer circumstances.